2020
DOI: 10.1332/239788220x15934528490504
|View full text |Cite
|
Sign up to set email alerts
|

The views of carers, people living with dementia and healthcare practitioners about the value of online information and peer support

Abstract: This article reports on research into the development of a website (Caregiverspro-MMD) intended for carers and people living with dementia. Carers, people living with dementia and healthcare practitioners were invited to explore a prototype of the website. Information was sought about: whether they thought the website would be useful; the functions and resources @ would require; and their views about using an online resource. Interviews and focus groups identified support for engaging with peers online and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Participants in Boots et al's (2017) study made limited use of an online carers' forum, and were constrained by feelings of disloyalty in sharing information about their partners and a wish to avoid others' accounts of 'misery'; a reluctance to hear about other people's problems has been documented elsewhere (Davies et al, 2019;McKechnie et al, 2014;Stokes et al, 2014). Although not evident here, some people with dementia have also highlighted the need for separate spaces away from carers 'ranting' (Rodriquez, 2013;White et al, 2020). Further exploration of the optimal balance between shared and separate resources or spaces is therefore required.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Participants in Boots et al's (2017) study made limited use of an online carers' forum, and were constrained by feelings of disloyalty in sharing information about their partners and a wish to avoid others' accounts of 'misery'; a reluctance to hear about other people's problems has been documented elsewhere (Davies et al, 2019;McKechnie et al, 2014;Stokes et al, 2014). Although not evident here, some people with dementia have also highlighted the need for separate spaces away from carers 'ranting' (Rodriquez, 2013;White et al, 2020). Further exploration of the optimal balance between shared and separate resources or spaces is therefore required.…”
Section: Discussionmentioning
confidence: 87%
“…Early research with users highlighted the importance of diverse content, in which issues such as dementia and caring were considered alongside 'lighter' material (White et al, 2020); therefore, both formal and informal content was created. Some participants expressed preferences for serious or lighter material; however, many appreciated the range and balance of content:…”
Section: Providing Content Which Is Balanced In Tonementioning
confidence: 99%
See 1 more Smart Citation
“…These challenges included, but were not limited to, caregiving demands, especially for those in the workforce, technical issues, and program design. In contrast to previous studies, our review did not identify caregivers’ concerns about the privacy and confidentiality of their information [ 54 , 55 ]. We found that although caregivers, especially those living in remote areas, perceived web-based psychoeducation programs as flexible, caregiving demands precluded many working caregivers from participating.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important group who could be expected to be among the most frequent, often daily, visitors to care homes. While the diversity of internet use among older people should be acknowledged (White et al, 2020b), older people appear to be among those especially at risk of digital exclusion (Nguyen et al, 2021;Seifert et al, 2021), and may therefore experience particular difficulties in adopting online communication and staying in touch if unable to visit. However, they may also need to be able to maintain contact remotely at times, for example, during periods of ill health or if transport is unavailable.…”
Section: Strengths and Limitationsmentioning
confidence: 99%